Determining Interval Time of Maintenance in Bosowa Cement Indonesia using Reliability Method - Suyuti, Muhammad Arsyad; Nur, Rusdi (Politeknik Negeri Ujung Pandang, 2016)
Maintenance for machining and production facility is an important aspect to ensure a smooth production process. During this time, it was performed regular maintenance based on technical advice from supplier’s engines which just shows things in general without considering the actual operating conditions. This paper aims to plan the maintenance strategies for the Finish Mill unit based on reliability analysis by considering the target system reliability and cost of improving reliability. The data distribution obtained the most appropriate distribution. Based on the data obtained distribution parameters, then the function of the reliability of each part an be determined so that the value of the reliability of each part and the overall system for a specific time period can be calculated. The results showed that the failure or breakdown Mill Finish Unit was majority caused by the part of 561.BM1, 531.WF1, 531.BC6, 531.BC2, 531.BC1, 561.SR1 and 531.BC3. it means that need to focus o the reliability analysis to allocate their parts.